The concept of student interpersonal communication - Mufadhal Barseli; Kristinus Sembiring; Ifdil Ifdil; Linda Fitria (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2018)
Interpersonal communication skills are one competency of students to interact with others. Students who experience problems in interpersonal communication will be hampered in the process of developing creativity and increasing their academic achievement at school. This shows the need for efforts by counselors to develop the counseling service practices to increase students’ understanding of the importance of interpersonal communication and the factors that influence low interpersonal communication skills. This paper will introduce the basic concepts of interpersonal communication including; the concept interpersonal communication, the characteristics of interpersonal communication, the importance of interpersonal communication, interpersonal communication criteria, factors that effect interpersonal communication, the process of interpersonal communication, the purpose of interpersonal communication and, communication this can a reference.